Inverse U-shaped Association between Sleep Duration and Semen Quality: Longitudinal Observational Study (MARHCS) in Chongqing, China - Chen, Qing (Sleep, 2016)
STUDY OBJECTIVES: To investigate the association between sleep duration and semen parameters as well as reproductive hormone levels. METHODS: We designed a cohort of male college students in Chongqing, China. A total of 796 subjects were recruited in 2013 and 656 (82.4%) were followed up in 2014. Each time, semen and peripheral blood samples were collected for semen quality and reproductive hormone measurement. Sleep duration was estimated by revised Munich Chronotype Questionnaire. In 2014, sleep quality was also measured by Pittsburgh Sleep Quality Index (PSQI). RESULTS: There was a substantial inverse U-shaped association between sleep duration and two semen parameters (semen volume and total sperm number), with 7.0–7.5 h/day of sleep showing highest parameters. Either longer or shorter sleep was associated with decreased semen parameters in a dose-response manner (P = 0.002 and 0.001, respectively). Sleeping > 9.0 h was associated with a 21.5% (95% confidence interval 9.2, 32.2) reduction in semen volume and 39.4% (23.3, 52.1) reduction in total sperm number; sleeping ≤ 6.5 h was associated with 4.6% (−10.5, 22.3) and 25.7% (−1.2, 60.1) reduction. Increase of the two parameters was found in those who changed sleep duration toward 7.0–7.5 h/day from 2013 to 2014. The U-shaped association was independent from PSQI and was replicated in another dataset of 1,346 males. No association found between sleep duration and reproductive hormone. CONCLUSIONS: Either restricted or excessive sleep may impair semen quality. Further research is needed to validate this finding. CITATION: Chen Q, Yang H, Zhou N, Sun L, Bao H, Tan L, Chen H, Ling X, Zhang G, Huang L, Li L, Ma M, Yang H, Wang X, Zou P, Peng K, Liu T, Cui Z, Ao L, Roenneberg T, Zhou Z, Cao J. Inverse u-shaped association between sleep duration and semen quality: longitudinal observational study (MARHCS) in Chongqing, China. SLEEP 2016;39(1):79–86.